Current status of trans‐anal total mesorectal excision (TaTME) following the Second International Consensus Conference. (January 2016) - Motson, R. W.; Whiteford, M. H.; Hompes, R.; Albert, M.; Miles, W. F. A.; ,
Abstract: This article documents the consensus of an expert group of surgeons from the Second International Trans‐anal Total Mesorectal Excision (TaTME) Conference held in Paris in July 2014. It outlines three facets of the TaTME procedure: (i) the technique and its indications, (ii) training and adoption, and (iii) data collection and the TaTME registry.